The Position of Creditors of Individual Collateral Holders In Insolvency Law - Afilia Dinda Dhiya Ulhaq (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
This researcher aims to find out about the rights of creditors of individual collateral holders in the norms of Law No. 37 of 2004 on Insolvency and Delay of Debt Payment Obligations. The researcher's method uses norrmative law with a statutory problem approach and a conceptual approach. Broadly speaking, the position of individual guarantees in the norms of the Bankruptcy Law if the insurer and debtor are declared bankrupt simultaneously, then it is a concurrent creditor and all the assets of the insurer as bankruptcy property. In the process of managing and releasing bankruptcy property, that the position of concurrent creditors in the process of division of bankruptcy property is at the bottom, because in principle it can but if the creditors are many while the property is few, then potentially do not get the share or even if it can be very small percentage. So that the position of creditors of individual collateral holders who are concurrent creditors is very weak in the process and distribution of bankruptcy property. When the debtor is declared bankrupt while the insurer is not declared bankrupt, then all the assets of the insurer do not include bankruptcy property. So creditors have the right to make a default lawsuit in accordance with Article 1243 kuhper to the insurer, if the process and enactment of the debtor's bankruptcy property is insufficient creditor debt. The mechanism of fulfilling achievements to individual guarantee holder creditors, namely creditors can execute the collateral object directly without having to apply for bail and execution to the court, because after the bail object is registered with the guarantee institution, the certificate will be issued as a guarantee that has executory power.